Factors Contributing to the Failure of In Vitro Fertilization (IVF): A Review of Male, Female, and Laboratory-Related Causes - Abdolhussein M, Mudhafar (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Infertility is big problem with some couples, infertility is an inability to get pregnancy and live birth after one year of marriage. There are many causes for this problem. In vitro fertilization (IVF) is one of the process to treat infertility. In vitro fertilization is includes induction of the ovaries to produce numerous oocytes, than fertilize the oocytes and development of the embryo, finally transfer the embryo. The most important reasons for repeated failure in vitro fertilization (IVF) cycle are related to the male characteristics, such as low semen concentration low sperm motility and morphology of sperm, there is a relationship between sperm quality and IVF outcome. Most of the maternal factors that contribution in decrease implantation and IVF cycle are uterine anomalies, adhesions, septa, and many more. Other factors such as body mass index (BMI), and smoking status for failure IVF. In this study review some of the causes of failure In vitro fertilization.